De la argumentación a la demostración a través del planteamiento y la resolución de problemas matemáticos con programación - Casilimas Sánchez, Luis Gabriel (Universidad Antonio Nariño, 2022)
Mathematics education is becoming more and more enriched to the extent that several research groups, as evidenced in the different international congresses, continue to grow in the field of research, however it is notable that there are groups that are emerging recently, which leads us to think how you can continue advancing in mathematics education. The research aims to characterize the relationship between argumentation and demonstration through the approach and resolution of mathematical problems mediated by programming with students between twelve and thirteen years of age. The activity system is based on Jerome Bruner's discovery learning theory, the resolution of challenging mathematical problems and the use of programs such as Scratch, in which a programming language suitable for children is used, thus facilitating the learning process. meaningful learning, oriented from technology. The research uses a methodology based on a qualitative approach, with an action research design and a methodology specific to the activities. The implementation of the activity system fosters cognitive development in students, the development of mathematical thinking, the construction of arguments, the relationship between argumentation and demonstration, creativity, autonomous learning, cooperative work, the use of programming and the creation of algorithms, the results obtained from this research suggest that the argumentation gives rise to the demonstration that is developed throughout the process and the way to show the solutions of the problems is through programming